Hydration properties and kinetic characteristics of blended cement containing lithium slag powder. (July 2021) - Zhai, Mengyi; Zhao, Jihui; Wang, Dongmin; Wang, Yiren; Wang, Qibao
Abstract: Lithium slag (LS) powder is a potential supplementary cementitious material due to its large content of active aluminosilicate minerals. To clarify the properties of LS powder as a supplementary cementitious material, the ionic dissolution properties of LS powder and the hydration properties and kinetic process of blended cement containing LS powder were studied in this paper. ICP was used to analyze the dissolution of Si 4+, Al 3+ and Ca 2+ ions in LS powder in the simulated cement alkali environment, and the mineral composition of the dissolved LS powder was analyzed by XRD. The results showed that SiO2 and Al2 O3 were the main active sources of LS powder and that an increase in the alkaline solution temperature promoted the dissolution of silicate in the LS powder and breaking of the Si–O and Al–O bonds. The hydration characteristics of blended cement were studied by isothermal calorimetry combined with the K-D model. The results showed that LS powder reduced the structural compactness of the hardened cement paste to varying degrees in the early stage of hydration, but in the later stage of hydration, the high content of S in the LS powder promoted the formation of rod-shaped ettringite in the hydration product. The proper amount (10%) of LS powder made the paste structure more compact. As determined by the hydration kinetic analysis, the hydration process of blended cement can be divided into crystal nucleation and growth (NG), phase boundary reaction (I) and diffusion (D) processes, and the rate of crystal nucleation is far greater than the rates of the phase boundary reaction and diffusion. According to the SEM results, the structure of blended cement is more compact when 10% LS powder was mixed in the cementitious system. Highlights: The ionic dissolution properties of lithium slag (LS) powder were discussed. The hydration kinetics of blended cement containing LS powder were studied. The microstructure of blended cement containing LS powder were analyzed.